Assessing E-Business at Small and Medium-Sized Travel Agencies - Noor, Any; Novianti, Syifaa; Suryana, Marceilla; Amalia, Sholihati (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article presents an analysis by using an electronic commerce model. The model was tested in 31 small and medium-sized travel agencies in West Java, Indonesia. In the second year, we conducted a qualitative approach by establishing a focus group discussion (FGD). The content analysis was applied to obtain a clear result of various information and resources of the FGD. The results were analyzed using NVivo 10 with a process of data reduction and showing that, in terms of technological and organizational preparation, most travel agencies have managed the electronic business from customer relationship management to the system of operations.